2013
DOI: 10.1017/s1041610213001403
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative and psychiatric overlap in frontotemporal lobar degeneration: a case of familial frontotemporal dementia presenting with catatonia

Abstract: The behavioral variant of frontotemporal dementia (FTD) begins with psychiatric symptoms, including changes in personal conduct and/or interpersonal behavior. Prior to developing cognitive impairment, differentiating FTD from primary psychiatric disorders, like schizophrenia, can be challenging. This paper presents a case of traumatic brain injury with subsequent depression and catatonia. Initial response to electroconvulsive therapy and lorazepam suggested primarily psychiatric pathology. Subsequent symptom p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…Additionally, the association between bvFTD and FTLD‐TDP type C has not been shown, so this case would be atypical in that regard. Several cases of clinical FTD with catatonic syndrome have been reported . but these were not pathologically examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the association between bvFTD and FTLD‐TDP type C has not been shown, so this case would be atypical in that regard. Several cases of clinical FTD with catatonic syndrome have been reported . but these were not pathologically examined.…”
Section: Discussionmentioning
confidence: 99%
“…but these were not pathologically examined. Interestingly, among such reports, a study identified the abnormal expansion of the C9ORF72 gene . It has been pointed out that there is a relatively strict correlation between C9ORF72 expansion (and also some other gene mutations) and the neuropathological change in FTLD‐TDP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 We report a case with a complex differential diagnosis between persistent residual catatonia symptoms and bvFTD, and we review the approach to this neuropsychiatric challenge. 2,3 In addition, catatonia can also be a presenting symptom of bvFTD.…”
mentioning
confidence: 99%
“…Cardinal catatonic features commonly overlap with advanced dementia [9]. Case reports of this composite presentation abound in the literature [10,11]. Even iatrogenic cases, due to the use of anti-dementia drug donepezil, were also reported [12].…”
mentioning
confidence: 99%